Pemberdayaan Ekonomi Umat : “Pemanfaatan Lingkungan Disekitar Rumah Untuk Budidaya Bayam Brazil Di Era Pandemi” - Tri Yahya Budiarso; Charis Amarantini; Guruh Prihatmo (Servirisma, 2022)
Brazilian spinach is a type of spinach that has not been widely consumed and cultivated by the Indonesian people even though it has excellent health benefits and is easy to cultivate. This Brazilian spinach cultivation training aims to empower the community during the pandemic by utilizing the land around the house or planting it in pots. The training participants were members of the GKI and GKJ churches from DIY and Central Java as well as some from Eastern Indonesia. Training participants are limited to 20 people with strict health protocols. The training materials are in the form of providing theory and direct practice in preparing seeds, media and planting as well as education about the benefits of brazil spinach for health. The results of this training were in the form of polybags containing spinach seeds that the participants had successfully harvested to take home and cultivate in their respective homes. Assistance for the Brazilian spinach cultivation process is carried out online through the WhatsApp group social media.